Manipueira no controle de Meloidogyne incognita e no rendimento da figueira (Ficus carica L.) cv. Roxo de Valinhos no oeste paranaense - Formentini, Heloísa Maria (2009)
In Brazil one of the main pathogens that affect the culture of the fig is the root-knot nematode Meloidogyne incognita. Thus the present study was the objective to evaluate the effect of manipueira, produced in the west paranaense, in the control of nematode Meloidogyne incognita in the culture of fig cv. Roxo de Valinhos, and verify your viability in areas that produce this fruit infested with this nematode. The experiment was conducted in a rural property located in Marechal Cândido Rondon - PR and infested with M. incognita. The experimental design was completely randomized to four treatments (such as water and witness the manipueira diluted in water at 10%, 25% and 50%) and five repetitions. Each fig tree was considered a repetition and was distributed randomly inside the area. Was applied on a monthly volume of four liters of liquid per plant over 13 months of experimentation. J2 forms weeds were counted per 100 cc of soil before the begining of applications and after each application. Soil samples were collected in the radius of projection of the crown of the fig trees to a depth of 0-20 cm. The mass of the fig fruit was computed in accordance with each crop. As the results, the treatments with manipueira to 25% and 50% caused a further reduction in the number of J2/100 cc of soil and the production of fruits, treatment with manipueira to 25% was higher than other treatments